The Impact of School Operational Assistance (BOS) on Student Expenditure and Scores - Kurniawan, Randi; Rakhmawati, Rakhmawati (Jurnal Ekonomi Indonesia, 2022)
This study aims to analyze the impact of the provision of BOS on student expenditures and scores. Using the Indonesia Family Life Survey (IFLS) waves 4 and 5 data, the results of the analysis with the Difference-in-Difference (DID) method find that the provision of BOS has an impact on increasing student scores. A one percent increase of BOS funds, on average, will increase 2.4 points of student scores. Meanwhile, there is no evidence of the effect of BOS funds on student spending on education. The results of this study encourage the need for the government to evaluate the allocation of BOS funds in schools to reduce the burden of student spending on education.